An Abundant and Diverse New Family of Electron Bifurcating Enzymes With a Non-canonical Catalytic Mechanism - Schut, Gerrit J.; Haja, Dominik K.; Feng, Xiang; Poole, Farris L.; Li, Huilin; Adams, Michael W. W. (Frontiers in Microbiology, 2022)
Microorganisms utilize electron bifurcating enzymes in metabolic pathways to carry out thermodynamically unfavorable reactions. Bifurcating FeFe-hydrogenases (HydABC) reversibly oxidize NADH (E’ ~ −280 mV, under physiological conditions) and reduce protons to H2 gas (Eo’ −414 mV) by coupling this endergonic reaction to the exergonic reduction of protons by reduced ferredoxin (E’ ~ −500 mV). We show here that HydABC homologs are surprisingly ubiquitous in the microbial world and are represented by 57 phylogenetically distinct clades but only about half are FeFe-hydrogenases. The others have replaced the hydrogenase domain with another oxidoreductase domain or they contain additional subunits, both of which enable various third reactions to be reversibly coupled to NAD+ and ferredoxin reduction. We hypothesize that all of these enzymes carry out electron bifurcation and that their third substrates can include hydrogen peroxide, pyruvate, carbon monoxide, aldehydes, aryl-CoA thioesters, NADP+, cofactor F420, formate and quinones, as well as many yet to be discovered. Some of the enzymes are proposed to be integral membrane-bound proton-translocating complexes. These different functionalities are associated with phylogenetically-distinct clades and in many cases with specific microbial phyla. We propose that this new and abundant class of electron bifurcating enzyme be referred to as the Bfu family whose defining feature is a conserved bifurcating BfuBC core. This core contains FMN and six iron sulfur clusters and it interacts directly with Fd and NAD(H). Electrons to or from the third substrate are fed into the BfuBC core via BfuA. The other three known families of electron bifurcating enzyme (abbreviated as Nfn, EtfAB and HdrA) contain a special FAD that bifurcates electrons to high and low potential pathways. The Bfu family are proposed to use a different electron bifurcation mechanism that involves a combination of FMN and three adjacent iron sulfur clusters, including a novel [2Fe-2S] cluster with pentacoordinate and partial non-Cys coordination. The absolute conservation of the redox cofactors of BfuBC in all members of the Bfu enzyme family indicate they have the same non-canonical mechanism to bifurcate electrons. A hypothetical catalytic mechanism is proposed as a basis for future spectroscopic analyses of Bfu family members.